Smokeless Tobacco Use is "Replacing" the Smoking Epidemic in the South-East Asia Region. Issue 1 (22nd December 2017) - Suliankatchi, Rizwan Abdulkader; Sinha, Dhirendra N; Rath, Ramashankar; Aryal, Krishna K; Zaman, Mostafa M; Gupta, Prakash C; Karki, Khem Bahadur; Venugopal, Deneshkumar
Abstract: Background: The sustained anti-tobacco campaign initiated in response to the mounting evidence against tobacco smoking has driven tobacco companies and smokers to look for alternative choices, such as smokeless tobacco (SLT) products. If this strategy advances, it could undermine several gains made by the campaign over the years. Our objective was to examine the trends in the prevalence of different tobacco types in three countries (Bangladesh, India, and Nepal) of South-East Asia. Methods: Data from national surveys were used to estimate the trends of weighted and age-standardized prevalence (along with 95% CI) of different tobacco products. The share of each tobacco type was then calculated as a percentage of total tobacco use for each time point and country. Results: In all the three countries, smoking prevalence declined (by 6% in Bangladesh, 3% in India, and 7% in Nepal) but SLT use increased (by 3% in Bangladesh, 6% in India, and 4% in Nepal) over the study period. SLT use increased irrespective of whether the total tobacco use increased or decreased. The share of SLT as a percentage of total tobacco use increased from 15% to 19% among Bangladeshi men, from 46% to 61% in India, and from 29% to 41% in Nepal. Conclusions: In South-East Asia, a clear shift in the product preference from smoking to SLT was noted. Misleading advertising by tobacco companies may be responsible for the increase in the SLT prevalence, which is as harmful as smoking. Countries should strengthen policies to restrict SLT usage and prevent the rise of its use. Implications: It has been documented that the smoking prevalence has been declining in most countries of the South-East Asia region where effective anti-tobacco laws have been implemented. But, due to a number of factors, the prevalence of smokeless tobacco has been increasing steadily, making the entire anti-tobacco movement less effective in terms of reducing the tobacco-attributable disease burden. In this context, this study has provided a detailed comparative analysis of the prevalence of smokeless tobacco use and smoking in three countries of the SEAR where such data were available. It can be clearly seen that the preference for smoking has shifted towards the smokeless tobacco in all the three study countries. This study recommends that tobacco control interventions should be aligned with the changing dynamics of the tobacco epidemic, and the need of the hour is placing restrictions of smokeless tobacco use so as to drive forward the gains of the anti-tobacco movement.